2015
DOI: 10.1007/s11255-015-1044-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting length of stay after robotic partial nephrectomy

Abstract: Introduction To investigate factors predictive of length of stay (LOS) after robotic partial nephrectomy (RPN) in an effort to identify patients suitable for RPN with overnight stay at outpatient surgical facilities. Materials and Methods Retrospective chart review of patients who underwent RPN at Memorial Sloan Kettering Cancer Center from January 2007 to July 2012 was conducted. Univariate and multivariate analyses were performed to identify the main predictors of LOS. The discrimination of the multivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Length of stay is an increasingly scrutinized surrogate for cost efficient care. Similar to our findings, prior studies have demonstrated the relationship between operative time and length of stay for partial nephrectomy 31,32,33 . The fastest operative time patients were hospitalized one less day on average than the slowest operative time patients (2.2 vs 3.3 days).…”
Section: Discussionsupporting
confidence: 92%
“…Length of stay is an increasingly scrutinized surrogate for cost efficient care. Similar to our findings, prior studies have demonstrated the relationship between operative time and length of stay for partial nephrectomy 31,32,33 . The fastest operative time patients were hospitalized one less day on average than the slowest operative time patients (2.2 vs 3.3 days).…”
Section: Discussionsupporting
confidence: 92%
“…Several retrospective studies showed larger tumor size was related to LOS>1 day and prolonged LOS after RANSS. 32,33 Correspondingly, R score of two points (tumor size>4cm) was associated with longer LOE in our study. The prediction formula could provide a reference for the evaluation of LOE and relatively safe time of discharge before surgery, especially helpful for hospitals without the condition of CEUS examination in an underdeveloped region.…”
Section: Discussionsupporting
confidence: 64%
“…Specifically, we found that over time, more RAPNs are being performed in patients with larger tumours, hypertension, diabetes and previous abdominal surgery. In RAPN, these factors are reported to lead to worse peri‐operative outcomes, with increasing tumour size leading to greater EBL, longer WIT, longer LOS and less trifecta achievement , major open abdominal surgery leading to more EBL and hypertension leading to worse immediate postoperative kidney function . Despite increased prevalence of these adverse factors over time, we show that from consecutive cases 50 to 300 among four surgeons, trifecta achievement continuously increased as WIT, EBL, peri‐operative blood transfusions and LOS continuously decrease beyond the surgeon's initial RAPN experience.…”
Section: Discussionmentioning
confidence: 73%